2008 7th International Conference on Mobile Business 2008
DOI: 10.1109/icmb.2008.18
|View full text |Cite
|
Sign up to set email alerts
|

Context-Sensitive Mobile Services for Police Officers: A Re-assessment of TAM

Abstract: This paper focuses on the explanatory value of context parameters and individual characteristics for preferences of police officers for mobile applications. Starting from adoption and acceptance (DoI and TAM), media choice and task-technology fit (TTF) theories, we collected data from police officers, who were asked which specific communication devices they preferred in specific situations. Our analyses show that the explanatory value of individual parameters is high when tested in a model that focuses exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Part of this is due to the model variables not including some of the specific characteristics unique to mCDS. Previous researchers have criticized the exclusive use of models to explain drivers or barriers for engagement with technology for this very reason [ 28 , 29 ]. Although existing models may explain an individual’s intention to use a given technology such as mCDS, they lack solutions to overcome context-specific barriers to engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Part of this is due to the model variables not including some of the specific characteristics unique to mCDS. Previous researchers have criticized the exclusive use of models to explain drivers or barriers for engagement with technology for this very reason [ 28 , 29 ]. Although existing models may explain an individual’s intention to use a given technology such as mCDS, they lack solutions to overcome context-specific barriers to engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that the use context closely relates to the intention to use a technology particularly when situated in a diversity of social contexts. Studying the police's adoption of mobile services, Bouwman et al (2008) found that context characteristics play an important role in the use of specific communication technologies. Van de Wijngaert and Bouwman (2009) found that the adoption and use of technology is context-dependent.…”
Section: Use Contextmentioning
confidence: 99%
“…Drawing from the Rational Choice Theory, privacy concern would have negative impact on intention to use. Therefore, H2: Privacy concern has negative effect on intention to use Present research found that intention to use depends on the situational context [29]. Users regarded as rational person, when facing with various LBS contexts, they would make the choice by priority of emergency and essentiality according with the "Time Management" theory.…”
Section: Theory Foundation and Hypothesismentioning
confidence: 99%